The sea peoples and their world : a reassessment - Oren, Eliezer D. (University Museum monograph, 2000)
This volume presents the results of the 1995 international seminar on the history and archaeology of the Sea Peoples. The 17 comprehensive articles, written by leading scholars in the fields of Egyptology, Hittitology, biblical studies, and Aegean, Anatolian, and Near Eastern archaeology, examine current methodologies and interpretations concerning the origin, migration, and settlement of the Sea Peoples against the overwhelming new archaeological record from sites throughout the Mediterranean basin and the Levant. Symposium Series 11University Museum Monograph, 108.